Transition of new dental graduates into practice: a qualitative study. (27th February 2015) - Ali, K.; Tredwin, C.; Kay, E.; Slade, A.
Abstract: Aims: The aims of this study were to explore the transition of new dental graduates to gain a deeper understanding of the merits and challenges of a mentored year for new graduates in general dental practice settings. Methods: The study was conducted in the south‐west region of England. Qualitative methods were used to engage a range of stakeholders in dental education including dental students, academics, general dental practitioners, new graduates, specialists and representatives of the postgraduate dental deanery. Purposive sampling was employed, and after ethical approval, participants were contacted through professional channels. All interview transcripts were transcribed verbatim. The data were imported into NVivo 10 (QSR International Pty Ltd) and analysed thematically. Results: Sixteen participants representing a variety of stakeholder groups were interviewed. The participants shared their perceptions and experiences regarding the transition new dental graduates into dental practice. The challenges and benefits are discussed along with strategies to facilitate a smooth transition. Conclusions: This study provides an insight into experience of a mentored year for new dental graduates in general practice settings. Foundation training provides a structured introduction into general practice and serves as a safety net before new graduates gain further independence in clinical practice.